Metamizole is a Moderate Cytochrome P450 Inducer Via the Constitutive Androstane Receptor and a Weak Inhibitor of CYP1A2. Issue 6 (19th January 2021) - Bachmann, Fabio; Duthaler, Urs; Meyer zu Schwabedissen, Henriette E.; Puchkov, Maxim; Huwyler, Jörg; Haschke, Manuel; Krähenbühl, Stephan
Abstract : Metamizole is an analgesic and antipyretic drug used intensively in certain countries. Previous studies have shown that metamizole induces cytochrome (CYP) 2B6 and possibly CYP3A4. So far, it is unknown whether metamizole induces additional CYPs and by which mechanism. Therefore, we assessed the activity of 6 different CYPs in 12 healthy male subjects before and after treatment with 3 g of metamizole per day for 1 week using a phenotyping cocktail approach. In addition, we investigated whether metamizole induces CYPs by an interaction with the constitutive androstane receptor (CAR) or the pregnane X receptor (PXR) in HepaRG cells. In the clinical study, we confirmed a moderate induction of CYP2B6 (decrease in the efavirenz area under the plasma concentration time curve (AUC) by 79%) and 3A4 (decrease in the midazolam AUC by 68%) by metamizole. In addition, metamizole weakly induced CYP2C9 (decrease in the flurbiprofen AUC by 22%) and moderately CYP2C19 (decrease in the omeprazole AUC by 66%) but did not alter CYP2D6 activity. In addition, metamizole weakly inhibited CYP1A2 activity (1.79‐fold increase in the caffeine AUC). We confirmed these results in HepaRG cells, where 4‐MAA, the principal metabolite of metamizole, induced the mRNA expression of CYP2B6, 2C9, 2C19, and 3A4. In HepaRG cells with a stable knockout of PXR or CAR, we could demonstrate that CYP induction by 4‐MAA depends on CAR and not on PXR. In conclusion, metamizole is a broad CYP inducer by an interaction with CAR and an inhibitor of CYP1A2. Regarding the widespread use of metamizole, these findings are of substantial clinical relevance.